The Effect of Project-Based Method on Improving the English-Speaking Skills: English - Nuris Akhmad; Dwi Nur Hadiyansa (JOEY: Journal of English Ibrahimy, 2026)
In this era, Madrasah Aliyah students must have skills to compete with others. One of them is English speaking skill. Madrasah Aliyah students must have the English-speaking skills necessary to face challenges worldwide. However, due to the lack of learning strategies that support activeness and communication skills, these skills are still underdeveloped. This study aims to evaluate the effect of implementing a project-based method on the English-speaking skills of Madrasah Aliyah students in Lumajang Regency. A quantitative approach with a quasi-experimental design was used in this study with a pretest-post-test and control group design. An English-speaking ability test was conducted to collect data, and the pretest and post-test results of the experimental and control groups were the data sources. English speaking ability between the two groups differed on average, and a t-test at a significance level of 0.05 was conducted for data analysis. Madrasah Aliyah students throughout Lumajang Regency were the subjects of this study, who were selected purposively based on the characteristics of the study. In this study, the tentative assumption is that, compared to conventional learning approaches, the project-based method has a significant effect on students' English-speaking ability. The findings are used for students, teachers, researchers and others to use and improve the method in the process of teaching and learning, & for further research.